China's quarter-century struggle with a nuclear North Korea with a focus on its strategic calculation. Issue 3 (8th July 2019) - Kim, Jih-Un
Abstract : Purpose: The purpose of this paper is to describe how China's approach to a nuclear North Korea has changed and find key variables that explain the changes. Design/methodology/approach: This paper adopts the traditional qualitative method, referring to different types of reliable and authoritative Chinese and English scholars, books and articles. Findings: Although China has accumulated distrust of North Korea and reprimanded the regime for its nuclear program, it has never ignored the strategic value or balance – especially vis-à-vis the USA – the neighboring country provides for it. And for that matter, it has been keen to prevent North Korea from bypassing it and getting closer to the USA. With this strategic calculation in mind, China has mostly made gestures in implementing the UN sanctions against North Korea, though not always. Originality/value: This paper proves that China's strategic calculation has been a constant key variable that explains its approach toward a nuclear North Korea since the inception of the issue in the early 1990s.